Diabetes Care in Venezuela - Ramfis Nieto-Martínez (Ubiquity Press, 2016)
Background: The incidence of type 2 diabetes (T2D) and its economic burden have increased in Venezuela, posing difficult challenges in a country already in great turmoil. Objectives: The aim of this study was to review the prevalence, causes, prevention, management, health policies, and challenges for successful management of diabetes and its complications in Venezuela. Methods: A comprehensive literature review spanning 1960 to 2015 was performed. Literature not indexed also was reviewed. The weighted prevalence of diabetes and prediabetes was estimated from published regional and subnational population-based studies. Diabetes care strategies were analyzed. Findings: In Venezuela, the weighted prevalence of diabetes was 7.7% and prediabetes was 11.2%. Diabetes was the fifth leading cause of death (7.1%) in 2012 with the mortality rate increasing 7% per year from 1990 to 2012. In 2012, cardiovascular disease and diabetes together were the leading cause of disability-adjusted life years.T2D drivers are genetic, epigenetic, and lifestyle, including unhealthy dietary patterns and physical inactivity. Obesity, insulin resistance, and metabolic syndrome are present at lower cutoffs for body mass index, homeostatic model assessment, and visceral or ectopic fat, respectively. Institutional programs for early detection and/or prevention of T2D have not been established. Most patients with diabetes (∼87%) are cared for in public facilities in a fragmented health system. Local clinical practice guidelines are available, but implementation is suboptimal and supporting information is limited. Conclusions: Strategies to improve diabetes care in Venezuela include enhancing resources, reducing costs, improving education, implementing screening (using Latin America Finnish Diabetes Risk Score), promoting diabetes care units, avoiding insulin levels as diagnostic tool, correct use of oral glucose tolerance testing and metformin as first-line T2D treatment, and reducing health system fragmentation. Use of the Venezuelan adaptation of the transcultural Diabetes Nutrition Algorithm for lifestyle recommendations and the Latin American Diabetes Association guidelines for pharmacologic interventions can assist primary care physicians in diabetes management.